Perubahan Kinerja Keuangan Privatisasi BUMN - Supriyanti, Wiwik (Jurnal Keuangan dan Perbankan, 2000)
This research investigates the effect of privtization the state owned goverment focus to evalution the level successful privazition relatid with frim finance performence. The objective of this research are measure Â financial pervomance privatized through the compare between performance before and after privatization. This study uses financial ratio to measure perfomance financial of privatization. To measure financial performance this research use financial ratio ananlysis base on characteristic profitability, effectivity operation effectivity asset , leverage and effeciency operation. The result showed that financial performance increase afterÂ  privatization. Ratio of profitability operation (ROS) experrienced increase , meanwhile efficiency operation and decreasing debt ratio to asset. This result imply that the BUMN in indonesian can improve financial performance through privatization wiht indicate efficiency operation